Analisis Kesiapan Guru Pendidikan Agama Islam dalam Pelaksanaan Kurikulum Merdeka pada Madrasah - Neneng Fauziah; Wazin Wazin; Wasehudin Wasehudin; Yuyun Rohmatul Uyun; Abdul Muin (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2025)
This study aims to analyze the readiness of PAI teachers in implementing the Independent Curriculum, supporting and inhibiting factors, and efforts made to improve its implementation. The study used a case study method with a qualitative approach at MTs Negeri 2 Tangerang and MTs Yabika Jambe, Tangerang Regency. Data were collected through observation, interviews, and documentation involving four PAI teachers as the main subjects, as well as the head of the madrasah, deputy head of curriculum, and head of the foundation as key informants. The results of the study showed that at MTs Negeri 2 Tangerang, PAI teachers were cognitively, psychologically, and financially ready, supported by the DIPA budget, ASN/PPPK status, and government policies. The main obstacles included teacher workload, time constraints, and inadequate IT facilities. Meanwhile, at MTs Yabika Jambe, teachers' cognitive and financial readiness were considered sufficient, while psychological readiness was considered ready, supported by the foundation's commitment, internet access, and community support. Inhibiting factors include limited learning time, financial constraints, and suboptimal understanding of the Merdeka Curriculum concept. Efforts made by both madrasas include Merdeka Curriculum training, development of differentiated RPP and P5RA, collaboration with madrasah principals and other teachers, utilization of digital technology, and involvement of parents and the community.